A TV no ecossistema dos onívoros digitais - Américo, Marcos [UNESP] (My University, 2015)
A quick setup of the digital environment that occurs in these first decades of the twentyfirst century has involved the use of electronic devices for consume content both at home, at work and on the go (ComScore, 2011). The emergence of this vast multiplatform digital landscape impels to know of individual and complementary use of these devices with ubiquitous nature or not. The widespread adoption of smartphones, tablets and other connected devices via internet makes users / consumers of these devices to feed a diet based on a constant flow of digital content across different platforms. The objective of this paper is to describe the role of television in the context of the Media Ecology which is established by the "digital omnivores" a new group of consumers whose name, according Canavilhas (2013, p.03), "is related with the platforms that consumers use to access the Internet, but also to the type of individual and multiplatform consumption they do.”

A rápida configuração do meio-ambiente digital que ocorre nestas primeiras décadas do século XXI tem envolvido o uso de dispositivos utilizados para consumir simultaneamente conteúdos nos espaços domésticos, laborais e também períodos de trânsito ou mobilidade (ComScore, 2011). O surgimento desta vasta paisagem digital multiplataforma impele a se conhecer as formas de utilização individual e complementar destes dispositivos de natureza ubíqua ou não. A ampla adoção de smartphones, tablets e outros aparatos conectados via internet faz com que os usuários/consumidores destes dispositivos se alimentem de uma dieta baseada em um fluxo constante de conteúdos digitais em diferentes plataformas. O objetivo deste texto é descrever o papel da TV no contexto da Ecologia da Mídia que se instaura diante da figura dos “onívoros digitais” um novo grupo de consumidores cuja denominação, de acordo com Canavilhas (2013, p.03), “está relacionada com as plataformas que estes consumidores usam para aceder à Internet, mas também com o tipo de consumo individual e multiplataforma que fazem.”
Keywords: Media ecology; Television; Digital omnivores; Media and technology; Ecologia dos meios; Televisão; Onívoros digitais; Mídia e tecnologia